Parallel texts from "Sweden a pocket guide" - Dahlberg, Simon; Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Parallel texts in form of the book "Sweden a pocket guide", translated to several languages. The material has been downloaded from the website of Immigrantinstitutet.

In 2017 only the Swedish version with translations to other EU languages (English, French and Croatian) were downloaded. In 2019 versions in the other languages (Arabic and Russian) were downloaded too.
What was downloaded were pdf files. The txt files that are available are the result of running the pdf files through the pdftotext command from an ubuntu shell.

Parallella texter i form av boken "Sverige en pocketguide" översatt till flera språk. Materialet har laddats ned från Immigrantinstitutets webbplats

I 2017 nedladdades bara den svenska versionen med översättningar till andra EU-språk (engelska, franska och kroatiska). I 2019 laddades versionerna på övriga språk (arabiska och ryska).
Det som nedladdades var pdf-filer. De txt-filer som finns tillgängliga är resultat ur en körning av kommandot pdftotext i ubuntu-skal.
Parallella texter från "Sverige en pocketguide"
Keywords: Emigration and Immigration; Utvandring och invandring; Migration; Migration; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur; Cultural Studies; Kulturstudier